A Proposed Syllabus for the Integrated Course in an English Education Department - Rochmahwati, Pryla; Kasnun; Pratama, Januari Rizki (LPPM Universitas PGRI Semarang, 2025)
This study aimed to develop a novel and practical syllabus for the Integrated Course subject designed explicitly for English Education Department students at IAIN Ponorogo. Using Borg and Gall's Research and Development (R&D) model, the research followed a systematic approach that included needs analysis, planning, prototype development, expert validation, product trials, and finalization. A key innovation in this syllabus is its integration of three distinct syllabus types: competency-based, content-based, and task-based. The syllabus includes 14 carefully sequenced topics, progressing from the simplest to the most complex, covering essential Listening, Reading, Speaking, and Writing areas. Offered as an 8-credit course with four meeting hours per week, it incorporates active and cooperative learning methods, emphasizing student-centered instruction. Another novel feature is the use of varied instructional media—audio, visual, and audio-visual materials—that connect students' prior experiences with the course content, making learning more dynamic and relatable. Assessment in the syllabus is comprehensive, combining both product and process evaluations to provide a well-rounded measurement of student progress. Expert validation and field testing confirmed that the final product is practical and highly applicable for the first-semester English Education students at IAIN Ponorogo, offering a tailored and impactful learning experience.